Oesophageal acid clearing: One factor in the production of reflux oesophagitis - Stanciu, C. (1974)
Oesophageal acid clearing has been measured by counting the number of swallows needed to raise the lower oesophageal pH from 1·5 to 5·0 after instilling 15 ml 0·1 N hydrochloric acid. Normal subjects all had a result less than 12, as did asymptomatic patients with hiatal hernias. Patients with symptomatic gastrooesophageal reflux tended to have abnormal acid clearance, as did those with oesophageal motility disorders. Acid clearance correlated well with the mean duration of spontaneous episodes of acid reflux during 15-hour continuous recordings of lower oesophageal pH. Abnormal acid clearance was improved by raising the bedhead, by medical treatment for oesophagitis, and by metoclopramide. We conclude that abnormal acid clearing may result from disturbed oesophageal motility and render patients with these disorders susceptible to reflux oesophagitis. However, it also seems that gastrooesophageal reflux may lead to impaired acid clearance, both by creating abnormal motility and by effects on the oesophageal wall, and thus lead to a `vicious-spiral' oesophagitis. In treating gastrooesophageal reflux, attention must be paid to improving acid clearance.